L. J. du Plessis as “Politieke Profeet” - Potgieter, P. J. J. S. (Koers, 1981)
In I960, after serious differences of opinion with the Party leaders on matters of policy, the late Prof. L. J. du Plessis was expelled from the National Party. Since then, some of his views have become accepted policy, and others, such as for example the idea of a constellation of Southern African states, enjoy national scrutiny at the moment. In the present quest for a new constitutional dis pensation for South Africa, his views are still valuable. An issue for which he gained wide notoriety especially among the political leaders of the day, was his uncompromising rejection of the element of white supremacy in the policy of the National Party. In this he clashed especially with Dr. Verwoerd. His views on the problems of South African politics as well as the foundational bases on which these views rested, are discussed in this article.